1,3-Bis{(+)-(S)-[1-(1-naphthyl)ethyl]iminomethyl}benzene dichloromethane solvate - Espinosa Leija, Armando (International Union of Crystallography, 2009)
In the title compound, C(32)H(28)N(2)·CH(2)Cl(2), the complete Schiff base and solvent molecules are both generated by crystallographic twofold axes, with the two C atoms of the former and the C atom of the latter lying on the rotation axis. The central benzene ring is substituted with two chiral groups including imine functionalities, with the common E configuration. The dihedral angle between the central benzene ring and the terminal naphthalene ring is 45.42 (9)° and that between the two naphthalene rings is 89.16 (8)°. The conformation of the Schiff base allows solvent molecules to fill the voids in the crystal, affording a stable 1:1 solvate, but the solvent interacts poorly with the Schiff base, as reflected by its rather high displacement parameters.